(untitled) (The Review of Diabetic Studies, 2025)
Background: Current prognostic tools for breast cancer, such as TNM staging, have limitations in capturing the systemic inflammatory and nutritional dimensions of the disease, which significantly influence patient outcomes. Inflammatory markers like C-reactive protein (CRP) and albumin, as well as their composite scores, have emerged as promising, cost-effective prognostic tools. Objective: This systematic review and meta-analysis aimed to comprehensively evaluate the prognostic value of CRP, albumin, the CRP-to-albumin ratio (CAR), and related composite scores (mGPS, PNI) in breast cancer patients, and to synthesize evidence on interventions that modify these biomarkers. Methods: A PRISMA-compliant systematic review was conducted. A comprehensive search of PubMed and the Cochrane Library (2010–2024) identified observational studies and randomized controlled trials (RCTs) reporting associations between these biomarkers and survival outcomes (OS, PFS, DFS). Data on study characteristics, biomarker measurements, and clinical outcomes were extracted. Quality was assessed using Cochrane RoB 2 tool. Results: The synthesis of evidence from 27 studies demonstrated robust prognostic significance for CRP and albumin. Elevated CRP predicted shorter progression-free survival in metastatic disease (e.g., during CDK4/6 inhibitor therapy) and increased breast cancer risk in pre-diagnostic settings. Low serum albumin was a strong, independent predictor of worse disease control, DFS, and OS across all stages. Composite scores integrating both markers—notably the modified Glasgow Prognostic Score (mGPS) and CAR—showed superior prognostic power. Patients with mGPS 2 had a more than twofold increased mortality risk (HR = 2.056) and a drastically reduced 10-year OS (22% vs. 71% for mGPS 0). RCTs confirmed the modifiability of CRP through interventions such as weight loss (35–44% reduction), exercise ( 30% reduction), and specific supplements (synbiotics, ω-3 fatty acids). Conclusion: CRP, albumin, and their derived ratios provide significant, independent prognostic information beyond traditional staging in breast cancer. Their integration into clinical practice offers a simple, cost-effective strategy for enhanced risk stratification, treatment response monitoring, and personalized supportive care. The demonstrated modifiability of these biomarkers through lifestyle and pharmacological interventions opens avenues for novel therapeutic strategies aimed at improving patient outcomes.